Pengaruh Profitabilitas, Struktur modal dan Arus Kas Terhadap Harga Saham dengan Ukuran Perusahaan Sebagai Variabel Moderasi BEI Periode 2015 – 2018 - Widya Darman; Atik Djajanti (Sekolah Pascasarjana Perbanas Jakarta, 2021)
This study aimed to analyze the effect of profitability (ROE), capital structure (DER) and cash flows on stock price to the firm size as variable moderation capital structure on stock price in company construction sub-sector listed on the Indonesia Stock Exchange during the year 2015 to 2018. The purposive sampling technique, the company sampled in this study was 8 construction companies. This study uses panel data regression models and types of secondary data from 2015 to 2018. Besides, it also tested the assumptions on the regression model. The research concludes that profitability significant positive effect on stock prices, capital structure significant negative effect on stock prices and cash flow does not have a significant effect on stock prices. While the firm size can moderate to weaken the negative effect of capital structure on stock prices.